2011
DOI: 10.1016/j.jacc.2010.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Glycoprotein IIb/IIIa Inhibitors During Elective Coronary Revascularization

Abstract: In the current era of elective PCI performed with stents and thienopyridines, GPIs provide clinical benefit. These agents reduce nonfatal myocardial infarction without a notable increase in major bleeding; however, they increase the risk of minor bleeding. All-cause mortality is not reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(8 citation statements)
references
References 62 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…The rate of death or myo-cardial infarction at 30 days and 6 months was 5.10% versus 7.52% and 7.51% versus 10.45% in the treatment versus the control groups, respectively. In one of the most recent assessments of the effects of αIIbβ3 blockers, Winchester et al 75 analyzed the results of 22 randomized studies with 10 123 patients undergoing PCI with stenting, who were treated routinely with ADP receptor antagonists (thienopyridines). This analysis showed that at 30 days, patients receiving αIIbβ3 antagonists had a significant reduction in myocardial infarction, 5.1% versus 8.3% in the control group without a significant increase in major bleeds, 1.2% versus 0.9%.…”
Section: Current Usage Of αIibβ3 Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of death or myo-cardial infarction at 30 days and 6 months was 5.10% versus 7.52% and 7.51% versus 10.45% in the treatment versus the control groups, respectively. In one of the most recent assessments of the effects of αIIbβ3 blockers, Winchester et al 75 analyzed the results of 22 randomized studies with 10 123 patients undergoing PCI with stenting, who were treated routinely with ADP receptor antagonists (thienopyridines). This analysis showed that at 30 days, patients receiving αIIbβ3 antagonists had a significant reduction in myocardial infarction, 5.1% versus 8.3% in the control group without a significant increase in major bleeds, 1.2% versus 0.9%.…”
Section: Current Usage Of αIibβ3 Antagonistsmentioning
confidence: 99%
“…However, overall mortality was not reduced. 75 Ongoing trials using αIIbβ3 inhibitors are focused primarily on reduction of side effects (eg, reduction of bleeding, dosage optimization for patients with renal dysfunction, alternative ways of infusion, treatment of severe sepsis in pneumonia patients).…”
Section: Current Usage Of αIibβ3 Antagonistsmentioning
confidence: 99%
“…Unfractionated heparin has been widely used for anticoagulation during percutaneous coronary intervention (PCI). The addition of glycoprotein IIb/IIIa inhibitors to unfractionated heparin has been shown to reduce peri-procedural ischemic events compared with heparin alone; however, this approach can increase bleeding risk [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are several reports on the effect of perioperative myocardial damage reduction and prognosis improvement about these drugs. [ 25 27 ] Also as Picchi et al [ 28 ] are trying to show, bivalirudin may have the effect of reducing the thrombus of the culprit lesion to such an amount that OCT imaging can detect in the acute phase of STEMI. These drugs may decrease thrombus volume, improve the quality of OCT image, and further reduce the incidence of FNR.…”
Section: Discussionmentioning
confidence: 99%